Peer Victimization and Problematic Online Game Use Among Chinese Adolescents: The Dual Mediating Effect of Deviant Peer Affiliation and School Connectedness - Li, Hao; Gan, Xiong; Xiang, Guo-Xing; Zhou, Ting; Wang, Pinyi; Jin, Xin; Zhu, Congshu (Frontiers in Psychology, 2022)
Abundant evidence has proved an association between peer victimization and problematic online game use. However, the underlying mechanisms of this relation are still under-investigated. Grounded in the ecological system theory, this study examined whether deviant peer affiliation and school connectedness mediated the association between peer victimization and adolescent problematic online game use. A sample of 698 Chinese adolescents completed questionnaires regarding peer victimization, problematic online game use, deviant peer affiliation, and school connectedness, of which 51.58% were boys. Path analyses indicated that peer victimization was positively associated with problematic online game use, and this link could be mediated by deviant peer affiliation and school connectedness. The findings identify the potential underlying mechanism by which peer victimization is associated with adolescent problematic online game use, which has important implications for theory and prevention.